KETAHANAN SUMBERDAYA GENETIK JAGUNG SULAWESI TENGGARA TERHADAP CEKAMAN KEKERINGAN PADA BERBAGAI FASE VEGETATIF - WIJAYANTO, TEGUH; GINTING, CANDRA; BOER, DIRVAMENA; AFU, WA ODE (Jurnal Agroteknos, 2014)
Maize crops experiencing water stress can experience cell damage, loss of turgor, closed stomata, plant leaf roll then wilt. Germination and vegetative growth are thought to be a very sensitive phases in relation to the availability of water, because it can influence subsequent growth processes. This study aimed to determine the potential tolerance of Southeast Sulawesi’s maize genotypes to drought stress at different vegetative growth phases. This study was based on completely randomized design (CRD) with factorial pattern consisting of two factors: the first factor composed of 9 local maize genotypes of Southeast Sulawesi and 1 national variety (cv. Arjuna), while the second factor was drought stress at different vegetative growth phases, consisting of four levels ie: C0 = plants irrigated with 100 % water availability during the growth phase, C1 = Stress for 5 days , at 21-26 days old (vegetative phase), C2 = Stress for 5 days starting at panicle emergence (early flowering stage), and C3 = Stress for 5 days starting 2 weeks after silking. Research results showed that Genotype (G) treatment significantly influenced all observed growth variables (at age 21 and 42 days after planting, DAP), except for the variable of number of leaf, age 21 DAP. However, water stress treatment (C) only significantly affected plant height variable, at the age of 42 DAP. In general, G6 and G7 genotypes tended to have a higher crop and trunk diameter than the other genotypes. Contrary, G3 genotype tended to have shorter crop and smaller stem diameter than the other genotypes. There are indications that the drought stress treatment (C) significantly inhibited the growth of maize crops. Keywords: drought strees, maize genotypes, tolerance, and vegetative phases